Mononuclear pyrazine-2-carbohydrazone metal complexes: Synthesis, structural assessment, thermal, biological, and electrical conductivity studies - Bansod, Ashish; Bhaskar, Ravindra; Ladole, Chandarshekhar; Salunkhe, Nilesh; Thakare, Kanchan; Aswar, Anand (European Journal of Chemistry, 2022)
Mononuclear complexes of VO(IV), Cr(III), Fe(III), MoO2(VI), WO2(VI), and UO2(VI) with pyrazinecarbohydrazone ligand (N’-(1-(5-chloro-2-hydroxyphenyl)ethylidene)pyrazine-2-carbohydrazide) were synthesized and the prepared complexes were characterized by elemental analysis, magnetic susceptibility, powder X-ray analysis, various spectroscopic techniques (IR, 1H NMR, 13C NMR, and Mass spectra), SEM, and thermal analysis. VO(IV) complex was additionally characterized by ESR study. The ligand behaves as a dibasic tridentate, coordinating through the phenolate oxygen, azomethine nitrogen, and enolate oxygen atoms towards the central metal ion. The analytical data suggest 1:1 metal to ligand stoichiometry for all complexes. The physicochemical data suggested octahedral geometry to Cr(III), Fe(III), MoO2(VI), WO2(VI), and UO2(VI) complexes while square pyramidal to VO(IV) complex. The SEM analysis indicated the presence of well-defined crystals free from any shadow of the metal ion on their external surface with particle sizes of greater than 10 μm. Various kinetics and thermodynamic parameters are calculated using Coats-Redfern method and on the basis of half decomposition temperature the thermal stability order of complexes was found to be Cr(III) < WO2(VI) < Fe(III) < MoO2(VI) < VO(IV) < UO2(VI). The solid-state electrical conductivity of compounds was measured in their pellet form in the temperature range form 313-373 K. The conductivity data vary exponentially with the absolute temperature and obey Arrhenius equation indicating their semiconducting behavior. The antibacterial as well as antifungal activities of ligand and its metal complexes were evaluated in vitro against Gram positive bacteria (S. aureus and B. subtilis) and Gram-negative bacteria (E. coli and S. typhi.) and fungal strains (C. albicans and A. niger). The activity data revealed metal complexes are found to be more active than the ligand.